Observational study of pediatric cochlear implant recipients: Two-year follow-up outcomes - ÇİPRUT, AYŞE AYÇA (My University, 2023)
Objective: The aim of this study was to evaluate the improvements in quality of life and auditory performance via a descriptive report using patient-related outcomes measures in a group of children with cochlear implants (CI). Methods: This was a longitudinal and retrospective study based on the analysis of patient records of a total of 28 children with CI, 18 of whom had bilateral (64.3%) and 10 had unilateral (35.7%). The study included repeated within-subject measures of Hearing Implants Quality of Life (CuHI-QoL), Categories of Auditory Performance (CAP-II), Speech, Spatial, and Qualities of Hearing scale-Parents’ version (SSQ-P) scales, and Implant Recipient Follow-up (IRF) form at 6-month intervals from baseline up to 24 months. Results: During the 2-year follow-up assessments, all children with CI showed statistically significant improvement over time in their CAP-II, SSQ-P, CuHI-QoL, and IRF scores (p<0.001). The most significant increase in scores occurred within the first six months following the baseline and then continued to increase gradually at a slower pace over time. A moderate negative relationship was found between the age of implantation and SSQ-P and family satisfaction scores of IRF (p<0.05). Conclusions: Family expectations, overall well-being, quality of life, auditory, and verbal skills increase positively with earlier CI intervention. Moreover, the subjective assessment results showed that parents-positive attitudes toward implantation, and willingness to recommend it to others have steadily increased in time. Although the cohort is relatively small and variable, the results offer a descriptive view to outcomes in real-world practice.

Amaç: Çalışmada bir grup koklear implantlı (Kİ) çocukta hastayla ilişkili değerlendirme anketleri yoluyla yaşam kalitesi ve işitsel performanstaki gelişmelerin değerlendirilmesi amaçlanmıştır. Yöntemler: Bu çalışma, 18’i çift taraflı (%64,3), 10’u tek taraflı (%35,7) olmak üzere toplam 28 Kİ’li çocuğun hasta kayıtlarının incelenmesini içeren uzunlamasına ve retrospektif bir çalışmadır. Çalışma, İşitsel İmplantlar Yaşam Kalitesi (İİYK), İşitsel Performans Kategorileri (İPKII), Konuşma, Uzaysal Algı ve İşitme Kalitesi ölçeği-Ebeveyn versiyonu (KUAİK-E) ölçekleri ve İmplant Kullanıcısı Takip (İKT) formunun açılıştan itibaren 24 ay boyunca her 6 ayda bir tekrarlanan öznel ölçümlerini içermektedir. Bulgular: İki yıllık takip değerlendirmeleri sırasında, Kİ’li tüm çocukların İPK-II, KUAİK-E, İİYK ve İKT skorlarında zaman içinde istatistiksel olarak anlamlı iyileşmeler görülmüştür (p<0,001). Puanlardaki en önemli artış, başlangıç çizgisini takip eden ilk altı ay içinde ortaya çıkmış, ardından zaman içinde daha yavaş bir hızda kademeli olarak artmaya devam etmiştir. İmplantasyon yaşı ile KUAİK-E ve İKT formu aile memnuniyet puanları arasında orta düzeyde negatif bir ilişki bulunmuştur (p<0,05). Sonuçlar: Aile beklentileri, genel refah, yaşam kalitesi, işitsel ve sözel beceriler erken Kİ müdahalesi ile olumlu yönde artmaktadır. Ayrıca, subjektif değerlendirme sonuçları ebeveynlerin implantasyona yönelik olumlu tutumlarının ve implantı başkalarına tavsiye etme isteklerinin zaman içinde istikrarlı bir şekilde arttığını göstermiştir. Kohort nispeten küçük ve değişken olmasına rağmen, sonuçlar gerçek dünyadaki uygulamalara ilişkin tanımlayıcı bir görüş sunması açısından önemlidir.
Pediatrik koklear implant kullanıcıları gözlemsel çalışması: İki yıllık takip sonuçları
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; auditory performance; Cochlear implants; family perspective; quality of life; speech development: Koklear implantlar; işitsel performans; konuşma gelişimi; aile perspektifi; yaşam kalitesi; Cochlear implants; auditory performance; speech development; family perspective; quality of life